DERAJAT COST STICKINESS SEKTOR PERBANKAN DAN PERTUMBUHAN EKONOMI - Windyastuti Windyastuti (University of Merdeka Malang, 2014)
This study aimed to analyze the effects of the growth on the stickiness cost in banking sector. The research datawas banking financial statements during 2001-2013 published at the Indonesian Capital Market Directory.The data included administration and general cost, banks Income and growth. This study used a dynamicpanel data regression with ordinary least square (OLS) estimation method. The results showed that cost ofadministration and general was sticky. Furthermore, the growth increased stickiness cost of administrationand general. The growth changed behavior of bank managers. When the growth increased, the bank managersincreased the amount of resources then administration and the general cost also increased although at the sametime banking income declined.